Quality of Life in Young Adults with ADHD Diagnosed in Adulthood: Systematic Review - Mazurkiewicz Rodríguez, Héctor José (2021)
Objective. Describe current studies on quality of life of young adults with ADHD diagnosed for the first time inadulthood, or who did not receive any type of treatment for this disorder. Method. a meta-synthesis was carried out investigations that report theoretical, methodological, and conclusive evidence of the object of study, following the recommendations on the Cochrane and PRISMA. Results. Six documents selected and analyzed out of 418 found showed that ADHD negatively affects the personal, emotional, physical, and material well-being of the young adult without diagnosis or treatment during the infantadolescent stage. The vast majority of young adults with ADHD, mainly those with comorbid disorders, have a poor perception of their quality of life.